PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE DRILL MATERI OPERASI HITUNG BILANGAN BULAT DAN PEMECAHAN MASALAH PADA MATA PELAJARAN MATEMATIKA DI KELAS V SDN 165726 TEBING TINGGI - Sutiah Sutiah (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2016)
This aim of this research is to improve learning result on mathematic subject  through drill method. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SD Negeri 165726 Tebing Tinggi which amounted to 37 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the problem posing method of mathematic subjects can improve student learning result characterized by increased mastery learning students, namely the first cycle (70,27%) , cycle II (89,18%) and complete learn the clasical equal to 89,18%.Key word : Drill, Learning Result, Mathematic